Extracurricular Role of The Scouting Movement in The Formation of Children's Character in The Digital Era - Alan Putra Pardede; Abdi Maulana; Abd Rahman Hakim Hasibuan; Abdullah Munawir Nasution; Fajar Siddik (Yayasan Adra Karima Hubbi, 2024)
Background. Scout extracurricular activities in elementary schools focus on improving students' skills, leadership, and sense of responsibility. The scout movement aims to build character and develop positive values through outdoor activities and practical learning. This is particularly important in the modern era, where children face challenges brought by digitalization. Purpose. The objective of this research is to explore the role of the Scout Movement in forming children's character in the modern era, specifically addressing how scouting activities can help children develop their character to face the challenges posed by digitalization. Method. This research employs a qualitative method using journal and book analysis as the primary data sources. An in-depth literature review is conducted to examine how the Scout Movement contributes to character development in children. Results. The analysis reveals that the scout movement significantly influences children's character formation, particularly in areas such as discipline, responsibility, cooperation, and independence. The literature reviewed indicates that the moral principles and life skills taught in scouting activities help counteract the negative effects of the digital era, such as technology addiction and decreased social interaction. Scout leaders are identified as key figures in modeling and facilitating the character-building process. Conclusion. The research concludes that the scout movement remains relevant and effective in shaping children's character, even in the face of digital era challenges. It contributes positively to personal and social development. To maximize the benefits of scouting in building character, the study suggests collaboration between schools, parents, and scout organizations.